OPTIMIZING STUDENT LEARNING OUTCOMES THROUGH THE FLIPPED CLASSROOM MODEL IN THIRD GRADE ELEMENTARY SCHOOL - Mutiara Laelatul Ulya; Abdul Karim; Sati (Jurnal Cakrawala Pendas, 2026)
This study was conducted because student achievement in the Natural and Social Sciences (IPAS) subject for third-grade students at SD Negeri 1 Susukan remains low. The use of conventional teaching methods has led to a decrease in student activity and independence during the learning process. This study aims to determine the effect of implementing the flipped classroom model on student achievement regarding the diversity of Earth’s surface features. The method used was quantitative with a one-group pretest-posttest pre-experimental design. This study involved 25 third-grade students. Data collection was carried out through observation, documentation, and tests consisting of pretests and posttests. Data analysis was performed using normality tests, n-gain tests, and t-tests for paired samples with the assistance of SPSS version 22. The results of the normality test indicate that the pretest and posttest data follow a normal distribution, with significance values of 0.193 and 0.063, respectively, as both are greater than 0.05. This study demonstrates that the implementation of the flipped classroom model can improve student learning outcomes. The N-Gain score of 0.7010 falls into the high category, while the N-Gain percentage of 70.0954 falls into the moderately effective category. Based on the results of the hypothesis test, a significance value of 0.000 was obtained, which is smaller than 0.05, and a calculated t-value of 14.400, which is greater than the table t-value of 2.064. Therefore, H0 is rejected and H1 is accepted. Thus, the flipped classroom model has a significant impact on student learning outcomes.